Hybridlandskap : nya möjligheter för offentliga platser i staden - Lund, Magdalena (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2005)
This project explores how artificial landscapes as parks and squares above ground can save space by using the vertical voids in urban environments and how they can create spatial and social as well as ecological qualities and connections.